El asedio al Raval: Una aproximación al pasado y presente de las transformaciones urbanísticas del barrio barcelonés - Miguel Fernandez (Oñati Socio-Legal Series)
Barcelona’s Public Space have been justified with the discourse of the need to put Barcelona into the market of the Global Cities. In these cities the production of profits is deputized at the service sector in prejudice of the industrial itself and it promotes the enormous entrance of property, financial and tourist capital. We came across a process of tertiarization which, in due time, requires a musealization of the city that makes it attractive for financial investors.